Patients' Experiences With Advance Care Planning and Decision-Making: An Interview Study in Finnish Hospital Palliative Care Wards - Kuusisto, Anne; Saranto, Kaija; Lähteenmäki, Katriina; Soikkeli-Jalonen, Anu; Haavisto, Elina (United Kingdom, 2025)
Aim and objective: This study described patients' experiences with advance care planning and decision-making in Finnish hospital palliative care wards.
Design: A descriptive qualitative study with semi-structured individual interviews.
Methods: The study group consisted of purposely selected patients in palliative care wards from two university hospital districts. A pretested interview guide was used. The interviews focused on three main themes with auxiliary questions. Data were gathered until data saturation was reached. The data were analysed using inductive content analysis.
Results: A total of 20 patients with cancer were interviewed. Patients' experiences with advance care planning in palliative care were grouped into three parent categories with subcategories: (1) Making plans for the end of life (need for psychosocial support in cancer disease and wish for goals of care discussion), (2) Symptom management planning (wish for pharmacological interventions for symptom management and wish for non-pharmacological interventions for symptom management) and (3) Palliative care coordination (need for discharge planning and wish for compatibility between team members). Patients' experiences with care decision-making in palliative care were grouped into two parent categories with subcategories: (1) healthcare professional as a care decision-maker (medical care decision-making, nursing care decision-making and inter-professional care decision-making) and (2) shared decision-making (need for patient involvement in shared decision-making and need for family member involvement in shared decision-making).
Conclusion: This study highlights the need for advance care planning and involvement in shared decision-making in palliative care from patient perspectives.
Relevance for clinical practice: The results from this study show that nurses must be critically concerned about the early and intentional initiation of palliative care.
Reporting method: The consolidated criteria for reporting qualitative studies checklist (COREQ) was used.
Patient or public contribution: The data consists of answers given by patients in interviews.